A NEW SPECIES OF THE GENUS AMESORHAGA (DIPTERA, DOLICHOPODIDAE) FROM THE BALTIC AMBER - Negrobov O.P.; Selivanova O.V. (My University, 2003)
The Recent genus Amesorhaga represented by new species A. vladimiri sp. nov., A. quadrispinosa sp. nov., A. bickeli sp. nov., A. longicerca sp. nov. is recorded in Baltic amber for the first time. An identification key is compiled for these species.